Juan Signes Codoñer, Escritura y literatura en la Grecia arcaica, Madrid, Ediciones Akal, 2004, 391 pp. (Minerva, 2019)
Review: Juan Signes Codoñer, Escritura y literatura en la Grecia arcaica, Madrid, Ediciones Akal, 2004, 391 pp.